Recent Advances in Cannabinoid Research - Robert B Laprairie; Willard J Costain (IntechOpen, 2019)
Scientific interest in cannabinoid research is currently experiencing a significant increase because of changing attitudes toward Cannabis and the evolving awareness of its pharmaceutical benefits. Coincidently, numerous jurisdictions are moving toward legalizing Cannabis and Cannabis-derived products, which reflects a larger global movement to understand Cannabis and its bioactive chemicals for their potential biomedical uses, harms, and economic value. Research activities are surging to fill important knowledge gaps in the field of cannabinoids as they continue to be identified. The purpose of this book is to summarize some leading areas of research in the cannabinoid field where knowledge gaps are actively being addressed. The research described herein spans basic biological and clinical research.
English
Keywords: Life Sciences; Neurochemistry; Neuroscience; Molecular Neuroscience